The Corporation as One of the Actions in Narcotics - Istiqlal Assaad, Andi (International Journal of Psychosocial Rehabilitation, 2020)
Corporate crimes are often referred to as organizational crimes or crimes committed by legal entities. Corporations can be criminally accounted for, because crimes committed by corporations have a huge loss to society, the environment and the country. In fact, some corporate cases are not only as a means to commit crimes, but are used as a means to collect proceeds of crime so that corporations benefit from the proceeds of crime. Indonesian criminal law has recognized corporations as subjects of criminal law since the emergence of Emergency Law No. 17 of 1951 concerning the Stockpiling of Goods, and Law No. 7 of Emergency of 1955 concerning Economic Criminal Act (Wet Economic Delichten). However, the Indonesian Criminal Code (KUHP) has not explicitly regulated corporate responsibility as a criminal offender. Therefore in practice law enforcement has a different interpretation of the corporation. In the context of narcotics distribution, corporations can act as producers. the container and those who distribute narcotics to the public. To ensnare corporations as narcotics awareness offenders, Article 130 of Law 35 of 2009 concerning Narcotics may be subject. These provisions can revoke business licenses and company management can also be given other legal actions.